Variability in the Qualitative and Quantitative Composition of Phenolic Compounds and the In Vitro Antioxidant Activity of Sour Cherry (Prunus cerasus L.) Leaves - Kristina Zymonė; Mindaugas Liaudanskas; Juozas Lanauskas; Miglė Nagelytė; Valdimaras Janulis (MDPI AG, 2024)
Sour cherry (Prunus cerasus L.) is a deciduous tree belonging to the Rosaceae Juss. family. Cherry leaves are an underutilized source of biologically active compounds. The aim of this study was to determine the composition of the phenolic compounds, as well as the total antioxidant activity, in leaf samples of P. cerasus cultivars and to elucidate the cultivars with particular phytochemical compositions. The phytochemical profiles of P. cerasus leaves vary significantly in a cultivar-dependent manner. The total content of identified phenolic compounds varied from 8.254 to 16.199 mg/g in the cherry leaves. Chlorogenic acid ranged between 1413.3 µg/g ('North Star') and 8028.0 µg/g ('Note'). The total content of flavonols varied from 4172.5 µg/g ('Vytenu zvaigzde') to 9030.7 µg/g ('Tikhonovskaya'). The total content of identified proanthocyanidins varied from 122.3 µg/g ('Note') to 684.8 µg/g ('Kelleris'). The highest levels of phloridzin (38.1 ± 0.9 µg/g) were found in samples of 'Molodezhnaya', while the lowest level of this compound was determined in the leaf samples of 'Turgenevka' (6.7 ± 0.2). The strongest antiradical (138.0 ± 4.0 µmol TE/g, p < 0.05) and reducing (364.9 ± 10.5 µmol TE/g, p < 0.05) activity in vitro was exhibited by the cultivar 'Vytenu zvaigzde' cherry leaf sample extracts. 'Kelleris', 'Note', and 'Tikhonovskaya' distinguish themselves with peculiar phytochemical compositions.